Higher-Order Convergent Iterative Method for Computing the Generalized Inverse over Banach Spaces - Xiaoji Liu; Fu Huang (Abstract and Applied Analysis)
A higher-order convergent iterative method is provided for calculating the generalized inverse over Banach spaces. We also use this iterative method for computing the generalized Drazin inverse in Banach algebra. Moreover, we estimate the error bounds of the iterative methods for approximating or .